Potential non-invasive detection of lesions in broiler femur heads: application of the DXA imaging system - Ramser, Alison; Greene, Elizabeth S.; Wideman, Robert; Dridi, Sami (Frontiers in Physiology, 2024)
Leg health is a significant economic and welfare concern for the poultry industry. Current methods of detection rely on visual assessment of legs and gait scores, as well as bone scoring during necropsy for full characterization. Additionally, current scoring of femurs only examines the external surface of the femoral head. Here, through the use of the Dual energy x-ray absorptiometry (DXA) imaging system, we show the presence of a necrotic region in femurs that would otherwise be considered healthy based on current evaluation procedures. Importantly, these lesions were present in almost 60% (22 of 37) of femurs scored normal for femur head necrosis (FHN). Additionally, these femurs showed greater bone mineral content (BMC) relative to weight compared to their counterparts with no lucent lesions (6.95% ± 0.20 vs. 6.26% ± 0.25; P=0.038). Identification of these lesions presents both a challenge and an opportunity. These subclinical lesions are likely missed in routine scoring procedures for FHN and can inadvertently impact characterization of the disease and genetic selection programs. Furthermore, this imaging system can be used for in-vivo, ex-vivo, and embryo (egg) and therefore constitutes a potential non-invasive method to early detection of bone lesions in chicken and other avian species.